On the validity of some species names of South American longhorn beetles (Coleoptera, Cerambycidae) - Monné, Miguel A.; Cupello, Mario (Zootaxa, 2015)
In this work, we propose the following taxonomic acts: in Elaphidiini, Ambonus variatus (Newman, 1841) is transferred to Centrocerum Chevrolat, 1861 and has as new junior synonyms Elaphidion elegans Chevrolat, 1861 and E. elegans var. hirsutum, var. jocosum, and var. puberulum, all names proposed by Chevrolat in 1861 as varieties and deemed here as available. In Acanthocinini, Leptostylus neivai Melzer, 1930 is raised from synonymy with L. ovalis Bates, 1863 based on morphological and distributional data. In Acanthoderini, a new synonymy is proposed between Acanthoderes leucogaeus Erichson, 1847 and A. virescens Fuchs, 1962, while in Anisocerini, Tetrasarus lineatus Bréthes, 1920 (described in Acanthoderini) is here considered a junior synonym of Caciomorpha genalis (Aurivillius, 1908).